Improved oxygen uptake efficiency slope in acute myocardial infarction patients after early phase I cardiac rehabilitation. Issue 3 (September 2017) - Tsai, Yun-Jeng; Li, Min-Hui; Chen, Chia-Hsin; Tuan, Sheng-Hui; Chen, Yi-Jen; Lin, Ko-Long
Abstract : A predischarge submaximal exercise test is often recommended after acute myocardial infarction (AMI) as part of phase I cardiac rehabilitation. In this study, a submaximal exercise parameter, oxygen uptake efficiency slope (OUES), was used to monitor the benefit of early mobilization within 48 h after AMI. An early mobilization protocol within 48 h after AMI has been initiated since 1 September 2012 in our center. Patients with onset time of AMI within 1 year before and 1 year after initiation of the early mobilization protocol were recruited for comparisons. Sixty patients were analyzed on the basis of this criterion, and were subjected to predischarge submaximal exercise tests. The OUES calculated with 100% exercise duration (OUES100 ) and calculated with the first 50% of exercise duration (OUES50 ) were obtained and analyzed. Both OUES100 and OUES50 of the AMI patients with early mobilization were significantly higher than those without early mobilization ( P =0.025 and 0.007, respectively). The OUES100 and OUES50 were also highly correlated ( r =0.891, P <0.001). The subgroup analysis using patients within 3 months before and 3 months after initiation of the protocol also showed a significant difference. OUES could be used to measure the exercise capacity and monitor the effect of phase I cardiac rehabilitation in patients soon after AMI. Early mobilization within 48 h following AMI significantly enhanced the patient's exercise capacity.